A List of Current Valid Blow Fly Names (Diptera: Calliphoridae) in the Americas South of Mexico with Key to the Brazilian Species - Kosmann, Cecília; Mello, Rubens Pinto de; Harterreiten-Souza, Érica Sevilha; Pujol-Luz, José Roberto (EntomoBrasilis, 2013)
The calliphorids flies comprise a heterogenous family found in all zoogeographical regions, with over 1,000 species and 150 genera described. The blow flies have a great medical and veterinary importance, and can be use in forensic science, especially in order to estimate the postmortem interval. Despite its wide distribution and importance, the group presents many taxonomic problems, and many conflicting records regarding the number of species in the Neotropical Region. In this paper, we list all species of Calliphoridae found in the Americas south of Mexico, based on reports in the literature between the years 1960 and 2012. There are 29 genera and 99 species recognized distributed in seven subfamilies: Calliphorinae (three genera and eight species), Chrysomyinae (seven genera and 28 species), Luciliinae (one genus and 17 species), Mesembrinellinae (nine genera and 33 species), Polleniinae (one genus and one species), Rhiniinae (one genus and one species), and Toxotarsinae (seven genera and 11 species). An identification key for the species that occur in Brazil is presented. Lista Atualizada de Nomes Válidos de Moscas-Varejeiras (Diptera: Calliphoridae) das Américas ao Sul do México, com uma Chave para as Espécies que Ocorrem no Brasil Resumo. Os califorídeos constituem uma família heterogênea encontrada em todas as regiões zoogeográficas, com mais de 1.000 espécies e 150 gêneros. As moscas-varejeiras possuem grande importância médica e veterinária, e podem ainda ser utilizadas nas ciências forenses, principalmente para estimar o intervalo pós-morte. Apesar da sua vasta distribuição e importância, o grupo apresenta muitos problemas taxonômicos e diversos registros conflitantes no tocante ao número de espécies presentes na região Neotropical. Neste artigo nós listamos todas as espécies de Calliphoridae encontradas nas Américas ao sul do México, baseadas em registros na literatura entre os anos de 1960 e 2012. Existem 29 gêneros e 99 espécies reconhecidas e distribuídas em sete subfamílias: Calliphorinae (três gêneros e oito espécies), Chrysomyinae (sete gêneros e 28 espécies), Luciliinae (um gênero e 17 espécies), Mesembrinellinae (nove gêneros e 33 espécies), Polleniinae (um gênero e uma espécie), Rhiniinae (um gênero e uma espécie) e Toxotarsinae (sete gêneros e 11 espécies). Uma chave de identificação para as espécies que ocorrem no Brasil é apresentada.